Development of ecolite blocks: utilising lightweight foamed concrete and palm oil fuel ash for sustainable construction - Adzmi, Seri Nuraliah; Zamry, Muhamad Khairul Ikhwan; Mohammad Fadzil, Nurfarah Hanim; Ismail, Sallehan (2024)
The innovative work "Development of EcoLite Blocks: Utilising Lightweight Foamed Concrete and Palm Oil Fuel Ash for Sustainable Construction" explores a sustainable approach to construction materials by incorporating environmentally friendly components. This study focuses on the development of EcoLite Blocks, which employ lightweight foamed concrete as the primary matrix, enhanced by the inclusion of palm oil fuel ash (POFA) as a partial replacement for conventional cement. The research aims to boost the mechanical properties and overall sustainability of the EcoLite Blocks through the utilisation of these alternative materials. By investigating the effects of POFA on the blocks' compressive strength, durability, and other pertinent properties, the work seeks to provide insights into a greener and more resource-efficient construction practice. The findings of this study hold potential implications for the construction industry’s efforts to reduce its environmental footprint while maintaining structural integrity and performance.